2014
DOI: 10.1002/2014gl061163
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of X‐ray emissions produced by stepping lightning leaders

Abstract: Intense and brief bursts of X-ray emissions have been measured during the stepping process of both natural cloud-to-ground (CG) and rocket-triggered lightning flashes. In this paper, we investigate theoretically the energy spectra of X-rays produced by the bremsstrahlung emission of thermal runaway electrons accelerated in the inhomogeneous electric field produced around lightning leader tips. The X-ray energy spectrum depends on the physical properties of the associated lightning leaders. Consequently, X-ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 23 publications
(49 reference statements)
7
34
0
Order By: Relevance
“…The proportionality coefficient in equation is obtained from the assumption that 10 11 photons with energies greater than 10 keV are produced in the case of a potential drop of 5 MV (see section 4). Following this procedure, we find that ξ ≃3.4 × 10 6 , which is consistent with the upper limit of 10 10 found by considering that all the streamers eventually constituting the streamer zone emit runaway electrons when they reached their limit of growth [ Celestin and Pasko , ; Xu et al , ]. The total number of photons corresponding to other potential drops is obtained through the assumption that this coefficient does not depend on the potential drop.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The proportionality coefficient in equation is obtained from the assumption that 10 11 photons with energies greater than 10 keV are produced in the case of a potential drop of 5 MV (see section 4). Following this procedure, we find that ξ ≃3.4 × 10 6 , which is consistent with the upper limit of 10 10 found by considering that all the streamers eventually constituting the streamer zone emit runaway electrons when they reached their limit of growth [ Celestin and Pasko , ; Xu et al , ]. The total number of photons corresponding to other potential drops is obtained through the assumption that this coefficient does not depend on the potential drop.…”
Section: Resultssupporting
confidence: 84%
“…This model simulates the dynamics of electrons propagating in air with energies from sub‐eV to GeV. The model has been used in recent studies to quantify thermal runaway electron emissions from streamer discharges [ Celestin and Pasko , ], properties of RREAs in homogeneous fields, and the acceleration of electrons in inhomogeneous fields produced by lightning leaders [ Celestin et al , ; Xu et al , , ]. The initial energy of the thermal runaway electrons is defined as 65 keV because those are believed to be produced by expanded streamers developing in the vicinity of the leader tip during the negative corona flash process [ Celestin and Pasko , ].…”
Section: Model Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…[], using an X‐ray pin‐hole‐type camera to image triggered lightning leaders near ground, suggested that the X‐ray source region for subsequent leaders that occurred in a preexisting channel, inferred to be below the leader tip, had a radius of 2 to 3 m. Xu et al . [] found that X‐ray bursts produced by 5 MV to 10 MV leaders would theoretically produce X‐ray burst spectra consistent with the experimental results reported by Schaal et al . [].…”
Section: Introductionsupporting
confidence: 85%
“…Similarly, with the same assumption for cases II, III and IV, the required numbers of streamers are ∼ 3.5 × 10 5 , ∼ 5 × 10 4 and ∼ 2.5 × 10 6 , respectively, and thus the UHF radiation energy would be ∼3 ×10 −4 J, ∼1 × 10 −5 J, and ∼2 × 10 −5 J, respectively. from the electrostatic consideration of the streamer zone (e.g., Celestin et al, 2015), 10 5 -10 7 streamers are required to give a potential drop of 2-20 MV near the lightning leader tip, which is commonly accepted for typical lightning leaders and also consistent with analysis of ground-based observation of X-rays produced by lightning (e.g., Xu et al, 2014). Specifically, the blue curve corresponds to the parameters: = 1.7 × 10 9 s −1 , = 7.5 × 10 7 s −1 , I CM0 = 0.44 A⋅m, and T 0 = 6 ns.…”
Section: 1029/2018gl080309mentioning
confidence: 74%